2020
DOI: 10.3389/fneur.2020.00281
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Patent Foramen Ovale in General Population and in Stroke Patients: A Narrative Review

Abstract: Introduction: Percutaneous closure of patent foramen ovale (PFO) in selected patients with cryptogenic cerebrovascular ischemic events (CEs) decreases the risk of recurrent stroke; however, optimal patient selection criteria are still under investigation. Candidates for PFO closure are usually selected from the pool of CE patients with a high risk of Paradoxical Embolism (RoPE) score. The RoPE score calculates the probability that PFO is causally related to stroke, based on PFO prevalence in patients with CE c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
75
2
11

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(91 citation statements)
references
References 82 publications
3
75
2
11
Order By: Relevance
“…Patients with COVID-19 pneumonia will almost certainly have some intra-pulmonary shunt [10][11][12]. Previous studies have reported that the prevalence of intra-pulmonary shunt is higher in patients with cryptogenic stroke (22%) than in matched controls (10%) [13].…”
Section: Editormentioning
confidence: 99%
See 3 more Smart Citations
“…Patients with COVID-19 pneumonia will almost certainly have some intra-pulmonary shunt [10][11][12]. Previous studies have reported that the prevalence of intra-pulmonary shunt is higher in patients with cryptogenic stroke (22%) than in matched controls (10%) [13].…”
Section: Editormentioning
confidence: 99%
“…However, discussion of paradoxical embolization, a well-recognised cause of stroke and systemic embolization [9,10,12], was conspicuously absent from their scoping review. We therefore suspect that this phenomenon is being overlooked during the current pandemic.…”
Section: Editormentioning
confidence: 99%
See 2 more Smart Citations
“…In young patients with cryptogenic stroke and a high Risk of Paradoxical Embolism (RoPE) score the presence of a PFO must be evaluated (24). TTE may detects certain normal anatomic variations of cardiac structures that may favor the formation of thrombi (25). The aneurysm of the interatrial septum, defined as >11 mm to >15 mm septum protrusion, is frequently associated with larger PFO (>4 mm size) and increases the risk of further stroke (26,27).…”
Section: Tte-pfo and Other Interatrial Changesmentioning
confidence: 99%